An ultra-ordered natural rubber-lignin chemically bonded composite material and a preparation method thereof
Patent Information
- Application Number
- CN202611393318.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-09
- Publication Date
- 2026-10-23
AI Technical Summary
[0006]针对现有技术存在的不足之处,本发明所要解决的技术问题是现有的天然橡胶与木质素复合材料需要液相反应体系且无法充分发挥木质素刚性分子骨架的补强潜力、复合材料综合性能提升幅度十分有限,提出一种通过无溶剂干法密炼工艺即可实现木质素-橡胶大分子原位共价键合的超聚态天然橡胶-木质素化学键合复合材料
(1)本发明全程采用超聚态天然橡胶(无塑炼工序),从根源上避免了橡胶大分子链的机械断裂与降解,完整保留了其超高分子量、窄分布(Mw/Mn≤1.7)、高规整度的原生超分子网络结构及优异的塑性保持率(PRI≥85);同时,通过对木质素进行胺基化改性,赋予填料高界面反应活性,使其与橡胶基体间由传统弱范德华力物理吸附转变为共价键化学键合,界面结合强度发生质变,应力传递效率大幅提升,从而最大化发挥生物质木质素刚性苯环骨架的本征补强潜能,显著超越传统物理共混体系的性能提升上限。
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer rubber composite materials and biomass resource modification technology, and particularly relates to a hyperpolymerized natural rubber-lignin chemically bonded composite material and its preparation method. Background Technology
[0002] With the rapid development of heavy-duty engineering machinery and the trunk heavy-duty logistics industry, the service conditions of heavy-duty all-steel radial tires are becoming increasingly complex and demanding. Extreme working conditions such as mining gravel roads, impacts from sharp and hard aggregates at construction sites, and the coupling effect of long-term static heavy loads and dynamic alternating friction have placed higher industry technical standards on the wear resistance, tear resistance, chipping and spalling resistance, and low dynamic heat generation performance of tire tread compounds. Natural rubber, with its unique strain-induced crystallization characteristics, high elasticity, and excellent fatigue resistance, has always been the irreplaceable core matrix polymer material for high-end heavy-duty tire tread compounds.
[0003] Industrial lignin is the most abundant naturally occurring aromatic biomass polymer produced as a byproduct of papermaking black liquor and biorefining residues. It possesses advantages such as a rigid benzene ring molecular skeleton, excellent wear and heat resistance, large raw material reserves, green and renewable nature, and low cost. It is an ideal green alternative to high-energy-consuming petroleum-based carbon black reinforcing filler and has extremely high potential for industrial application in the field of functional rubber modification.
[0004] Currently, lignin-modified natural rubber technology still has significant technical shortcomings: most technologies use ordinary commercial natural rubber or natural rubber latex as the matrix, and generally employ emulsion grafting and wet solution-liquid phase reaction systems. These processes consume large amounts of organic solvents and rely on exogenous chemical initiators to catalyze interfacial reactions, resulting in lengthy processes, large emissions of waste, high energy consumption, and complex post-purification and processing of the products, making it difficult to achieve continuous, large-scale industrial production. Furthermore, in existing publicly available technologies, in traditional lignin / rubber composite systems, the filler and rubber matrix rely solely on weak van der Waals forces to form a physical interface adsorption, resulting in low interfacial bonding strength and poor stress transfer ability. This fails to fully utilize the reinforcing potential of the rigid molecular framework of lignin, and the overall performance improvement of the composite material is very limited.
[0005] Therefore, there is an urgent need for a natural rubber-lignin chemically bonded composite material and its preparation method that can achieve in-situ covalent bonding of lignin-rubber macromolecules through a solvent-free dry mixing process. Summary of the Invention
[0006] To address the shortcomings of existing technologies, the technical problem to be solved by this invention is that existing natural rubber and lignin composite materials require a liquid-phase reaction system and cannot fully utilize the reinforcing potential of the rigid molecular skeleton of lignin, resulting in very limited improvement in the overall performance of the composite materials. This invention proposes a superpolymerized natural rubber-lignin chemically bonded composite material that can achieve in-situ covalent bonding of lignin-rubber macromolecules through a solvent-free dry mixing process.
[0007] To solve the aforementioned technical problem, the technical solution adopted by the present invention is as follows: A hyperpolymerized natural rubber-lignin chemically bonded composite material comprises: 80-100 parts of hyperpolymerized natural rubber and 5-20 parts of amino-modified lignin; in the composite material, the amino-modified lignin and the molecular chains of the hyperpolymerized natural rubber are covalently bonded through Schiff base bonds and / or amide bonds; the molecular weight distribution of the hyperpolymerized natural rubber is Mw / Mn≤1.7, the plasticity retention rate is PRI≥85, and the content of endogenous non-rubber components is 8%-9%.
[0008] In some embodiments, the amination lignin is prepared by the following method: dispersing raw lignin in water, adjusting the pH of the dispersion system to 10-12, adding an amination reagent, stirring at a constant temperature of 50-80°C for 2-6 h, neutralizing, washing, and drying to obtain the amination lignin; the mass ratio of the amination reagent to the raw lignin is 1:1.
[0009] In some embodiments, the amination agent is one of ethylenediamine, 1,6-hexanediamine, and diethylenetriamine.
[0010] In some embodiments, the raw material lignin is one of alkali lignin from the papermaking industry or enzymatically hydrolyzed lignin from biorefining.
[0011] In some embodiments, the composite material further includes: 45-50 parts of carbon black, 3-6 parts of rubber processing compounding activator, 1.5-3 parts of composite antioxidant, 1-2 parts of vulcanizing agent, and 1-2 parts of vulcanization accelerator.
[0012] In some embodiments, the carbon black is any one of tire-specific wear-resistant carbon black N134, N234, N220, N326, and N330; the rubber processing compound activator is prepared by uniformly blending zinc oxide and stearic acid at a mass ratio of 2:1; the composite antioxidant is a mixture of p-phenylenediamine antioxidant 6PPD and quinoline antioxidant TMQ at a mass ratio of 2:1; the vulcanizing agent is any one of powdered sulfur or insoluble sulfur OT-20; and the vulcanization accelerator is any one of sulfenamide rubber accelerators NS, DZ, and CZ.
[0013] This invention also discloses a method for preparing a superpolymerized natural rubber / lignin chemically bonded composite material, comprising: S1: The superpolymerized natural rubber, amino-modified lignin, rubber processing compound activator, and composite antioxidant are initially mixed, and then carbon black is added and mixed continuously to obtain the compounded rubber. S2: The compound obtained in S1 is sealed and left to stand for 4-5 hours to eliminate the residual shear stress inside the rubber compound. Then, the compound is mixed with vulcanizing agent and vulcanization accelerator and kneaded to prepare the final compound. S3: The final rubber compound is molded, vulcanized, cooled and demolded to obtain a composite material.
[0014] In some embodiments, in step S1, a closed internal mixer is used for segmented mixing. The rotor speed of the closed internal mixer is 45 r / min, and the initial internal mixing is performed for 25 s. After the entire carbon black filler is added at atmospheric pressure, the mixture is subjected to a second internal mixing for 35 s. The mixture is then continuously heated and sheared. When the rubber compound temperature reaches 150-160°C, the rubber is discharged. The total mixing time for a single batch is 3-5 min. In some embodiments, a closed internal mixer is used in step S2. The rotor speed of the closed internal mixer is 30 r / min, and the initial internal mixing is performed for 30 seconds. After the rubber compound is vented by lifting the plug to remove air bubbles, it is mixed again by pressing the plug. When the rubber compound is heated to 100-110°C, the rubber is discharged. The mixing time for a single batch is 2-4 minutes.
[0015] The present invention also discloses a heavy-duty all-steel radial tire, wherein the tire tread compound is made of the above-mentioned hyperpolymerized natural rubber / lignin chemically bonded composite material.
[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The present invention uses superpolymer natural rubber throughout the process (without plasticizing process), which avoids mechanical breakage and degradation of rubber macromolecular chains from the source, and fully preserves its ultra-high molecular weight, narrow distribution (Mw / Mn≤1.7), high regularity of native supramolecular network structure and excellent plasticity retention rate (PRI≥85); at the same time, by amination modification of lignin, the filler is endowed with high interfacial reactivity, so that the physical adsorption of lignin with rubber matrix is transformed from traditional weak van der Waals force physical adsorption to covalent chemical bonding, the interfacial bonding strength undergoes qualitative change, and the stress transfer efficiency is greatly improved, thereby maximizing the intrinsic reinforcing potential of the rigid benzene ring skeleton of biomass lignin, significantly exceeding the performance improvement limit of traditional physical blending system.
[0017] (2) This invention completely abandons the emulsion polymerization and organic solvent liquid-phase reaction system required for traditional lignin-modified rubber. It does not require the addition of any organic solvents or exogenous chemical initiators, but relies solely on the mechanical shear heat during dry mixing to trigger the in-situ covalent reaction of Schiff base / amide bonds between the amino-modified lignin and the hyperpolymerized natural rubber molecular chains. The overall process is concise, with no organic waste emissions, significantly reduced energy consumption, and minimal raw material loss. It can be directly adapted to existing rubber industry-standard closed-loop mixing unit production lines, requiring no additional equipment investment, with low barriers to entry and promising prospects for continuous large-scale industrial production. Detailed Implementation
[0018] The technical solutions in specific embodiments of the present invention will be described in detail and completely below. Obviously, the described embodiments are only some specific implementations of the overall technical solution of the present invention, and not all implementations. Based on the overall concept of the present invention, all other embodiments obtained by those skilled in the art fall within the protection scope of the present invention.
[0019] This invention provides a hyperpolymerized natural rubber-lignin chemically bonded composite material, comprising: 80-100 parts of hyperpolymerized natural rubber and 5-20 parts of amino-modified lignin; in the composite material, the amino-modified lignin and the hyperpolymerized natural rubber molecular chains are covalently bonded through Schiff base bonds and / or amide bonds; the hyperpolymerized natural rubber has a molecular weight distribution Mw / Mn≤1.7, a plasticity retention rate PRI≥85, and an endogenous non-rubber component content of 8%-9%. "Hyperpolymerized natural rubber" refers to a novel type of refined structured natural rubber prepared using a low-frequency, shear-free, low-temperature primary processing technology, distinct from ordinary commercial natural rubber (such as SCR5 and SCR10) prepared through standard granulation and high-temperature drying processes. Its key structural feature is that the macromolecular chains retain the integrity and regularity of the original supramolecular network structure of natural rubber. This invention utilizes hyperpolymerized natural rubber throughout the entire process (without a plasticizing process), fundamentally avoiding the mechanical breakage and degradation of the rubber macromolecular chains. It fully preserves the ultra-high molecular weight, narrow distribution (Mw / Mn≤1.7), highly regular native supramolecular network structure, and excellent plasticity retention (PRI≥85). Simultaneously, by amination modification of lignin, the filler is endowed with high interfacial reactivity, transforming the traditional weak van der Waals physical adsorption with the rubber matrix into covalent chemical bonding. This results in a qualitative change in interfacial bonding strength and a significant improvement in stress transfer efficiency, thereby maximizing the intrinsic reinforcing potential of the rigid benzene ring skeleton of biomass lignin and significantly exceeding the performance enhancement limit of traditional physical blending systems. Specifically, the interfacial covalent bonding between amination-modified lignin and hyperpolymerized natural rubber in this invention follows the following reaction mechanism: After alkaline activation-amination modification, a large number of active primary amine groups (-NH2) are introduced onto the surface of the lignin molecules. In the high-temperature shear environment of a closed internal mixer (rubber compound temperature 150–160°C), the active functional groups carboxyl groups (-COOH) and aldehyde groups (-CHO) retained at the ends of the hyperpolymerized natural rubber molecular chains undergo two types of chemical reactions with the primary amine groups on the surface of aminated lignin: the primary amine groups undergo nucleophilic addition-elimination reactions with the aldehyde groups to generate Schiff base covalent bonds containing imine bonds (-C=N-); the primary amine groups and carboxyl groups undergo dehydration condensation at high temperatures to form amide bonds (-CO-NH-). These two types of reactions can proceed spontaneously without external initiators under the synergistic effect of the localized high temperature and high stress concentration effect generated by the mechanical shearing during mixing.
[0020] Based on the aforementioned covalent bonding, this invention constructs a dual reinforcing network within the composite material: "physical entanglement of rubber molecular chains - covalent crosslinking of lignin." The ultra-high molecular weight and narrow molecular weight distribution of hyperpolymerized natural rubber ensure high-density physical entanglement between molecular chains, endowing the matrix with high elasticity and fatigue resistance. Aminolated lignin is anchored to the ends of rubber molecular chains via covalent bonds, and introduced into the rubber network with a rigid benzene ring backbone as crosslinking nodes, forming a reinforcing structure that combines rigidity and flexibility. The synergy of these two elements enables efficient stress transfer from the rubber matrix to the rigid lignin backbone, significantly enhancing interfacial bonding strength and greatly improving stress transfer efficiency.
[0021] The content of endogenous non-adhesive components (proteins, phospholipids, metal ions, etc.) is 8%–9%. Their role is to construct the native supramolecular network of rubber macromolecules through hydrogen bonding and ionic bonding, ensuring the high plasticity retention of the material. At the same time, the polar active sites such as carboxyl and aldehyde groups carried by proteins and phospholipids can assist in the interfacial chemical reaction with the primary amine groups of aminated lignin during dry mixing, thus strengthening the filler. Matrix interface bonding.
[0022] In some embodiments, amination lignin is prepared by the following method: raw lignin is dispersed in water, the pH of the dispersion system is adjusted to 10–12, an amination reagent is added, and the mixture is stirred at a constant temperature of 50–80°C for 2–6 h. After neutralization, washing, and drying, amination lignin is obtained; the mass ratio of the amination reagent to the raw lignin is 1:1. It is understood that those skilled in the art can adjust the process parameters within the above range according to actual conditions. For example, the reaction temperature can be 55°C, 60°C, 65°C, 70°C, 75°C, or any value within the above range, and the reaction time can be 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h, or any value within the above range.
[0023] In some embodiments, after the amination reaction is completed, the system is neutralized to neutral with dilute hydrochloric acid to remove unreacted raw materials and salt byproducts; the mixture is then washed and filtered three times each with deionized water and anhydrous ethanol, and dried under vacuum at 60°C to constant weight to prepare powdered highly active amination lignin.
[0024] In some embodiments, the amination agent is one of ethylenediamine, 1,6-hexanediamine, diethylenetriamine, or other similar organic compounds with an aliphatic (non-aromatic) molecular structure and containing two or more primary amino groups (-NH2).
[0025] In some embodiments, the raw material lignin is either alkali lignin from the papermaking industry or enzymatically hydrolyzed lignin from biorefining. Industrial lignin is the most abundant naturally occurring aromatic biomass polymer, a byproduct of papermaking black liquor and biorefining residues. It possesses advantages such as a rigid benzene ring molecular skeleton, excellent wear and heat resistance, large raw material reserves, green renewability, and low cost. It is an ideal green alternative to high-energy-consuming petroleum-based carbon black reinforcing fillers and has extremely high industrial application potential in the field of functional rubber modification. Both alkali lignin from the papermaking industry and enzymatically hydrolyzed lignin from biorefining are conventional industrial byproducts. The weight-average molecular weight (Mw) of alkali lignin is typically 1000–20000 Da, while that of enzymatically hydrolyzed lignin is typically 1500–8000 Da. Both molecules contain abundant phenolic hydroxyl groups, which can improve the dispersion performance of lignin under alkaline conditions. Modification is achieved by relying on the aldehyde and carboxyl active sites of the lignin molecule side chain to undergo an amino grafting reaction with the amination reagent. This invention does not have a strict limitation on the original molecular weight of lignin. As long as it has reactive aldehyde and carboxyl active sites, it can be used to prepare the highly active amino-modified lignin.
[0026] In some embodiments, the composite material further includes: 45-50 parts of carbon black, 3-6 parts of rubber processing compounding activator, 1.5-3 parts of composite antioxidant, 1-2 parts of vulcanizing agent, and 1-2 parts of vulcanization accelerator.
[0027] In some embodiments, the carbon black is any one of tire-specific wear-resistant carbon black N134, N234, N220, N326, and N330; the rubber processing compound activator is prepared by uniformly blending zinc oxide and stearic acid at a mass ratio of 2:1; the composite antioxidant is a mixture of p-phenylenediamine antioxidant 6PPD and quinoline antioxidant TMQ at a mass ratio of 2:1; the vulcanizing agent is any one of powdered sulfur or insoluble sulfur OT-20; and the vulcanization accelerator is any one of sulfenamide rubber accelerators NS, DZ, and CZ.
[0028] This invention also discloses a method for preparing a superpolymerized natural rubber / lignin chemically bonded composite material, comprising: S1: The superpolymerized natural rubber, amino-modified lignin, rubber processing compound activator, and composite antioxidant are initially mixed, and then carbon black is added and mixed continuously to obtain the compounded rubber. S2: The compound obtained in S1 is left to stand at room temperature in a sealed environment for 4-5 hours to eliminate residual shear stress inside the rubber compound. Then, the compound is mixed with vulcanizing agent and vulcanization accelerator and kneaded to prepare the final compound. S3: The final rubber compound is molded, vulcanized, cooled and demolded to obtain a composite material.
[0029] Existing lignin-modified natural rubber technologies suffer from significant technical shortcomings: most technologies use ordinary commercial natural rubber or natural rubber latex as the matrix, and generally employ emulsion grafting and wet solution-liquid phase reaction systems. These processes consume large amounts of organic solvents and rely on exogenous chemical initiators to catalyze interfacial reactions, resulting in lengthy processes, large emissions of waste, high energy consumption, and complex post-purification and processing of the products, making continuous, large-scale industrial production difficult. This invention completely abandons the emulsion polymerization and organic solvent-liquid phase reaction systems essential for traditional lignin-modified rubber. It requires no added organic solvents or exogenous chemical initiators, relying solely on the mechanical shear heat during dry mixing to autonomously trigger the in-situ covalent reaction of Schiff base / amide bonds between the amino-modified lignin and the hyperpolymerized natural rubber molecular chains. The overall process is concise, with no organic waste emissions, significantly reduced energy consumption, and minimal raw material loss. It can be directly adapted to existing closed-loop mixing mill production lines commonly used in the rubber industry, requiring no additional equipment investment, thus having a low barrier to entry and promising prospects for continuous, large-scale industrial production.
[0030] The compound is left to stand in a sealed container at room temperature (20-30℃) for 4-5 hours to eliminate residual shear stress and promote the uniform micro-dispersion of nanofillers.
[0031] In some embodiments, in step S1, a closed internal mixer is used for segmented mixing. The rotor speed of the closed internal mixer is 45 r / min, and the initial internal mixing is performed for 25 s. After the entire carbon black filler is added at atmospheric pressure, the mixture is subjected to a second internal mixing for 35 s. The mixture is then continuously heated and sheared. When the rubber compound temperature reaches 150-160°C, the rubber is discharged. The total mixing time for a single batch is 3-5 min. In some embodiments, a closed internal mixer is used in step S2. The rotor speed of the closed internal mixer is 30 r / min, and the initial internal mixing is performed for 30 seconds. After the air bubbles in the rubber compound are removed by lifting the plug, the mixture is mixed again by pressing the plug. When the rubber compound is heated to 100-110°C, the rubber is discharged at low temperature to prevent premature scorching. The mixing time for a single batch is 2-4 minutes.
[0032] The present invention also discloses a heavy-duty all-steel radial tire, wherein the tire tread compound is made of the above-mentioned hyperpolymerized natural rubber / lignin chemically bonded composite material.
[0033] To more clearly and in detail introduce the hyperpolymerized natural rubber-lignin chemically bonded composite material and its preparation method provided in the embodiments of the present invention, the following description will be based on specific embodiments.
[0034] Unless otherwise specified, all the following raw material proportions are by weight; all performance tests of the rubber compound comply with national standards: Shore A hardness (GB / T 531.1), tensile and fracture mechanical properties (GB / T 528), DIN abrasion (GB / T 9867), resilience (GB / T 1681), and dynamic thermomechanical properties (DMA) (GB / T 9870.1).
[0035] Example 1 10 g of alkali lignin was dispersed in 30 mL of deionized water, and sodium hydroxide solution was added to adjust the pH of the system to 11. The system was heated to 60 °C in a water bath, and 10 g of ethylenediamine was slowly added dropwise. The mixture was stirred and kept at a constant temperature for 4 h. After the reaction was completed, the system was cooled to room temperature, and the pH of the system was adjusted to neutral using dilute hydrochloric acid. The mixture was washed three times each with deionized water and anhydrous ethanol, and the filter cake was dried in a vacuum environment at 60 °C for 2 h to prepare aminated lignin.
[0036] Ten parts of the above-mentioned amino-modified lignin, 100 parts of superpolymerized natural rubber, 4 parts of zinc oxide, 2 parts of stearic acid, 2 parts of antioxidant 6PPD, and 1 part of antioxidant TMQ were put into a closed internal mixer. The rotor speed was set to 45 r / min, and the mixture was first pressed and mixed for 25 s. After lifting the plug, 50 parts of carbon black N134 were added and the mixture was pressed and mixed for 35 s. The temperature was continuously increased by shearing. When the rubber compound temperature reached 155℃, the rubber was discharged to obtain the in-situ bonded modified compound.
[0037] The bonded modified compound was left to stand in a sealed container at room temperature (20-30℃) for 4-5 hours to allow for stress relaxation and microscopic uniform dispersion of the filler. Subsequently, it was fed into a closed internal mixer with 2 parts of ordinary sulfur and 2 parts of accelerator NS. The rotor speed was 30 r / min, and the mixture was pressed and mixed for 30 s. After the venting was lifted, the mixture was pressed and mixed again. The compound was heated to 110℃ and discharged to obtain the final compound. The final compound was then vulcanized at 151℃ for 30 min to obtain the target composite material.
[0038] The performance of the samples in this embodiment was tested according to national standards, with each test referring to the following standards: Shore A hardness (GB / T 531.1), tensile and fracture mechanical properties (GB / T 528), DIN abrasion (GB / T 9867), resilience (GB / T 1681), and dynamic thermomechanical properties (DMA) (GB / T 9870.1). The test results showed that the Shore A hardness was 71.2, the tensile strength was 28.14 MPa, the elongation at break was 448%, the resilience was 53.8%, the DIN abrasion index reached 171%, and the tanδ at 60℃ was 0.1087. Compared with Comparative Example 1 without added aminated lignin, the DIN abrasion index of this embodiment increased by 4.9%, and the tanδ at 60℃ decreased by 6.1%. This verifies that under the solvent-free dry mixing system of this invention, aminated lignin can form a stable covalent cross-linking reinforcing network with hyperpolymerized natural rubber, effectively enhancing the wear resistance of the composite material and reducing the dynamic heat generation of the rubber compound.
[0039] Example 2 10 g of alkali lignin was dispersed in 30 mL of deionized water, and sodium hydroxide solution was added to adjust the pH of the system to 10. The mixture was heated to 80 °C in a water bath, and 10 g of 1,6-hexanediamine was slowly added dropwise. The mixture was stirred at a constant temperature and the reaction was maintained for 2 h. After the reaction was completed, the mixture was cooled to room temperature, and the pH of the system was adjusted to neutral using dilute hydrochloric acid. The mixture was washed three times each with deionized water and anhydrous ethanol, and the filter cake was dried in a vacuum environment at 60 °C for 2 h to prepare aminated lignin.
[0040] Five parts of the above-mentioned amino-modified lignin, 100 parts of superpolymerized natural rubber, 2 parts of zinc oxide, 1 part of stearic acid, 2 parts of antioxidant 6PPD, and 1 part of antioxidant TMQ were put into a closed internal mixer. The rotor speed was set to 45 r / min, and the mixture was first pressed and mixed for 25 s. After lifting the plug, 45 parts of carbon black N234 were added and the mixture was pressed and mixed for 35 s. The mixture was continuously sheared and heated until the rubber compound temperature reached 150℃. The rubber compound was then discharged to obtain the in-situ bonded modified compound.
[0041] The bonded modified compound was left to stand in a sealed container at room temperature (20-30℃) for 4 hours to allow for stress relaxation and microscopic uniform dispersion of the filler. Subsequently, it was fed into a closed internal mixer with 2 parts of ordinary sulfur and 2 parts of accelerator NS. The rotor speed was 30 r / min, and the mixture was pressed and mixed for 30 s. After the venting was lifted, the mixture was pressed and mixed again. The compound was heated to 100℃ and discharged to obtain the final compound. The final compound was then vulcanized at 161℃ for 20 min to obtain the target composite material.
[0042] Performance testing was conducted according to the testing standards of Example 1. The results showed that the Shore A hardness was 70.1, the tensile strength was 27.52 MPa, the elongation at break was 462%, the resilience was 54.2%, the DIN abrasion index reached 165%, and the tanδ at 60℃ was 0.1106. This example demonstrates that under low-dosage aminated lignin (5 parts), the dry in-situ chemical bonding system of this invention can still rely on covalent interface bonding to synergistically construct a physically entangled-covalently cross-linked dual reinforcing network with carbon black filler, achieving synergistic optimization of the composite material's wear resistance and low heat generation performance.
[0043] Example 3 10 g of alkali lignin was dispersed in 30 mL of deionized water, and sodium hydroxide solution was added to adjust the pH of the system to 12. The system was heated to 50 °C in a water bath, and 10 g of diethylenetriamine was slowly added dropwise. The mixture was stirred and kept at a constant temperature for 4 h. After the reaction was completed, the system was cooled to room temperature, and the pH of the system was adjusted to neutral using dilute hydrochloric acid. The mixture was washed three times each with deionized water and anhydrous ethanol, and the filter cake was dried in a vacuum environment at 60 °C for 2 h to prepare aminated lignin.
[0044] 20 parts of the above-mentioned amino-modified lignin, 80 parts of superpolymerized natural rubber, 4 parts of zinc oxide, 2 parts of stearic acid, 4 parts of antioxidant 6PPD, and 2 parts of antioxidant TMQ were put into a closed internal mixer; the rotor speed was set to 45 r / min, and the mixture was first pressed and mixed for 25 s; 50 parts of carbon black N330 were added after lifting the plug and then pressed and mixed for 35 s; the temperature was continuously increased by shearing, and the rubber compound was discharged when the temperature reached 160℃ to obtain in-situ bonded modified compound.
[0045] The bonded modified compound was left to stand in a sealed container at room temperature (20-30℃) for 4-5 hours to allow for stress relaxation and microscopic uniform dispersion of the filler. Subsequently, it was fed into a closed internal mixer with 1.5 parts of ordinary sulfur and 2 parts of accelerator DZ. The rotor speed was 30 r / min, and the mixture was pressed and mixed for 30 s. After the venting was lifted, the mixture was pressed and mixed again. The compound was heated to 100℃ and discharged to obtain the final compound. The final compound was then vulcanized at 161℃ for 30 min to obtain the target composite material.
[0046] Performance tests were conducted according to the testing standards of Example 1. The results showed that the Shore A hardness was 72.5, the tensile strength was 28.62 MPa, the elongation at break was 432%, the resilience was 52.5%, the DIN abrasion index reached 175%, and the tanδ at 60℃ was 0.1058. This example demonstrates that increasing the amount of aminated lignin added can further strengthen the covalent bond strength at the filler-rubber interface and further optimize the wear resistance and low dynamic heat generation performance of the composite material. Considering the economic cost of raw materials and the processing and molding performance of the rubber compound, the optimal addition range of aminated lignin was determined to be 10–20 parts by weight.
[0047] Example 4 10 g of alkali lignin was dispersed in 30 mL of deionized water, and sodium hydroxide solution was added to adjust the pH of the system to 10. The system was heated to 80 °C in a water bath, and 10 g of diethylenetriamine was slowly added dropwise. The mixture was stirred at a constant temperature and the reaction was maintained for 2 h. After the reaction was completed, the system was cooled to room temperature, and the pH of the system was adjusted to neutral using dilute hydrochloric acid. The mixture was washed three times each with deionized water and anhydrous ethanol, and the filter cake was dried in a vacuum environment at 60 °C for 2 h to prepare aminated lignin.
[0048] 15 parts of the above-mentioned amino-modified lignin, 80 parts of superpolymerized natural rubber, 2 parts of zinc oxide, 1 part of stearic acid, 3 parts of antioxidant 6PPD, and 1.5 parts of antioxidant TMQ were put into a closed internal mixer; the rotor speed was set to 45 r / min, and the mixture was first pressed and mixed for 25 s; 48 parts of carbon black N220 were added after lifting the plug and then pressed and mixed for 35 s; the temperature was continuously increased by shearing, and the rubber compound was discharged when the temperature reached 160℃ to obtain in-situ bonded modified compound.
[0049] The bonded modified compound was left to stand in a sealed container at room temperature (20-30℃) for 4-5 hours to allow for stress relaxation and microscopic uniform dispersion of the filler. Subsequently, it was fed into a closed internal mixer with 1.5 parts of ordinary sulfur and 2 parts of accelerator CZ. The rotor speed was 30 r / min, and the mixture was pressed and mixed for 30 s. After the venting was lifted, the mixture was pressed and mixed again. The compound was heated to 100℃ and discharged to obtain the final compound. The final compound was then vulcanized at 151℃ for 30 min to obtain the target composite material.
[0050] Performance tests were conducted according to the testing standards of Example 1. The results showed that the Shore A hardness was 71.8, the tensile strength was 28.35 MPa, the elongation at break was 440%, the resilience was 53.5%, the DIN abrasion index reached 173%, and the tanδ at 60℃ was 0.1075. This example verifies that aminated lignin prepared with different reaction process parameters and different aliphatic amination reagents can all be adapted to the solvent-free dry in-situ bonding system of this invention, stably improving the overall service performance of rubber composite materials.
[0051] Example 5 10 g of enzymatically hydrolyzed lignin was dispersed in 30 mL of deionized water, and sodium hydroxide solution was added to adjust the pH of the system to 12. The mixture was heated to 70 °C in a water bath, and 10 g of diethylenetriamine was slowly added dropwise. The mixture was stirred and kept at a constant temperature for 3 h. After the reaction was completed, the mixture was cooled to room temperature, and the pH of the system was adjusted to neutral using dilute hydrochloric acid. The mixture was washed three times each with deionized water and anhydrous ethanol, and the filter cake was dried in a vacuum environment at 60 °C for 2 h to prepare aminated lignin.
[0052] 15 parts of the above-mentioned amino-modified lignin, 90 parts of superpolymerized natural rubber, 3 parts of zinc oxide, 1.5 parts of stearic acid, 3 parts of antioxidant 6PPD, and 1.5 parts of antioxidant TMQ were put into a closed internal mixer; the rotor speed was set to 45 r / min, and the mixture was first pressed and mixed for 25 s; 50 parts of carbon black N326 were added after lifting the plug and then pressed and mixed for 35 s; the temperature was continuously increased by shearing, and the rubber compound was discharged when the temperature reached 155℃ to obtain the in-situ bonded modified compound.
[0053] The bonded modified compound was left to stand in a sealed container at room temperature (20-30℃) for 4-5 hours to allow for stress relaxation and microscopic uniform dispersion of the filler. Subsequently, it was fed into a closed internal mixer with 1.5 parts of ordinary sulfur and 2 parts of accelerator DZ. The rotor speed was 30 r / min, and the mixture was pressed and mixed for 30 s. After the venting was lifted, the mixture was pressed and mixed again. The compound was heated to 100℃ and discharged to obtain the final compound. The final compound was then vulcanized at 151℃ for 20 min to obtain the target composite material.
[0054] Performance tests were conducted according to the testing standards of Example 1. The results showed that the Shore A hardness was 71.5, the tensile strength was 28.42 MPa, the elongation at break was 445%, the resilience was 53.6%, the DIN abrasion index reached 174%, and the tanδ at 60℃ was 0.1070. This example demonstrates that the dry chemical bonding preparation process of the present invention has good versatility for both alkali lignin and enzymatically hydrolyzed lignin, two mainstream industrial by-product lignin raw materials.
[0055] Comparative Example 1 The difference between this comparative example and Example 1 is that no amino-modified lignin was added to the formulation, while the remaining raw material components, mixing and vulcanization preparation processes and process parameters are completely consistent with those of Example 1.
[0056] Performance tests were conducted according to the testing standards of Example 1. The results showed that the Shore A hardness was 69.8, the tensile strength was 27.36 MPa, the elongation at break was 463%, the resilience was 54.2%, the DIN abrasion index was 163%, and the tanδ at 60℃ was 0.1158. Comparison with the data from Example 1 shows that the stress transfer efficiency of the single carbon black physical reinforcement system is lower. Direct verification indicates that the covalently cross-linked network constructed from amino-modified lignin can synergistically enhance the physical reinforcement network of carbon black, significantly optimizing the abrasion resistance and dynamic heat generation properties of the compound.
[0057] Comparative Example 2 The difference between this comparative example and Example 1 is that the amino-modified lignin is replaced with an equal amount of unmodified native alkali lignin, while the remaining raw material components, all preparation processes and process parameters are completely consistent with Example 1.
[0058] Performance tests were conducted according to the testing standards of Example 1. The results showed that the Shore A hardness was 68.5, the tensile strength was 25.83 MPa, the elongation at break was 472%, the resilience was 52.1%, the DIN abrasion index was 155%, and the tanδ at 60℃ was 0.1195. Comparison with the data from Example 1 shows that unmodified industrial lignin and the hyperpolymerized natural rubber matrix can only form a weak van der Waals physical adsorption interface and cannot generate a stable covalent cross-linked structure. It is clear that lignin amination modification is a necessary prerequisite for achieving high-strength interface reinforcement of the filler in the dry mixing system of this invention.
[0059] Comparative Example 3 The difference between this comparative example and Example 1 is that the superpolymerized natural rubber is replaced in equal amounts with commercial standard natural rubber SCR10 (Chinese National Standard Rubber No. 10, which has a wide molecular weight distribution and Mw / Mn is usually ≥3.0). The remaining formulation components and the entire processing technology are completely consistent with Example 1.
[0060] Performance tests were conducted according to the testing standards of Example 1. The results showed that the Shore A hardness was 68.0, the tensile strength was 26.52 MPa, the elongation at break was 485%, the resilience was 50.5%, the DIN abrasion index was 152%, and the tanδ at 60℃ was 0.1182. Comparison with the data from Example 1 shows that ordinary commercial natural rubber with a wide molecular weight distribution has poor molecular regularity and its large molecular chains are easily degraded by mechanical shear, making it unsuitable for the dry in-situ bonding reaction system of this invention. Verifying the hyperpolymerized natural rubber matrix defined in the claims is a core and necessary technical condition for constructing an efficient dual-reinforcing network and preparing high-performance target composite materials.
[0061] As can be seen from the above embodiments and comparative examples, the composite material in this application achieves multiple performance indicators synergistically, making it suitable for extreme heavy-duty service conditions. Compared to a blank hyperpolymer rubber system with the same formulation but without added aminated lignin, the composite material of this invention exhibits a tensile strength increase of over 2.9%; a DIN abrasion index ≥ 165%; and a dynamic hysteresis loss factor tanδ ≤ 0.111 at 60℃. It simultaneously achieves synergistic optimization of three core properties: high mechanical strength, high abrasion resistance, and low dynamic heat generation, meeting the stringent service requirements of heavy-duty tires for impact resistance, wear resistance, and thermal degradation resistance in mining and unpaved road construction.
[0062] This application presents a novel solvent-free, dry, in-situ covalent bonding system, overcoming the bottleneck of mass production in wet processes. This invention completely eliminates the emulsion polymerization and organic solvent liquid-phase reaction systems essential for traditional lignin-modified rubber; it requires no added organic solvents or exogenous chemical initiators, relying solely on the mechanical shear heat of dry mixing to autonomously trigger the covalent reaction at the filler-rubber interface. The process is concise, with no organic waste emissions, low energy consumption, and minimal raw material loss; it can be directly adapted to existing closed-loop mixing unit production lines in the rubber industry, with low barriers to entry and easy industrial-scale continuous production.
[0063] This application utilizes rubber raw materials that fully retain the original supramolecular structure of hyperpolymerized rubber, breaking through the upper limit of physical blending reinforcement. The invention completely eliminates the plasticizing process of hyperpolymerized natural rubber, fundamentally avoiding the mechanical breakage of rubber macromolecular chains and fully preserving its ultra-high molecular weight, narrow distribution, and highly regular original supramolecular network. Through lignin amination modification, the filler is endowed with high interfacial reactivity, achieving covalent bonding reinforcement between the filler and the rubber matrix. The interfacial bonding strength is significantly enhanced, stress transfer efficiency is greatly improved, and the reinforcement potential of the biomass lignin rigid framework is maximized.
[0064] The technical solution in this application realizes the high-value resource utilization of industrial by-products, with wide raw material adaptability and rich application scenarios. This invention uses inexpensive industrial by-product lignin to partially replace high-energy-consuming petroleum-based carbon black, reducing fossil resource consumption and the carbon footprint of rubber product production; the process has good adaptability to alkali lignin, enzymatically hydrolyzed lignin, and various aliphatic amination reagents; the prepared composite material can be used to prepare heavy-duty tire tread rubber, heavy-duty rubber buffer pads, wear-resistant conveying hoses for mining, and other products, with a wide range of industrial applications.
Claims
1. A superpolymerized natural rubber-lignin chemically bonded composite material, characterized in that, include: The composite material comprises 80-100 parts of hyperpolymerized natural rubber and 5-20 parts of amino-modified lignin; in the composite material, the amino-modified lignin and the molecular chains of the hyperpolymerized natural rubber are covalently bonded through Schiff base bonds and / or amide bonds; the molecular weight distribution of the hyperpolymerized natural rubber is Mw / Mn≤1.7, the plasticity retention rate is PRI≥85, and the content of endogenous non-rubber components is 8%-9%.
2. The hyperpolymerized natural rubber-lignin chemically bonded composite material as described in claim 1, characterized in that, The amino-modified lignin was prepared by the following method: The raw material lignin was dispersed in water, the pH of the dispersion system was adjusted to 10-12, an amination reagent was added, and the reaction was carried out at a constant temperature of 50-80℃ for 2-6 h. After neutralization, washing, and drying, the amination lignin was obtained. The mass ratio of the amination reagent to the raw material lignin is 1:
1.
3. The hyperpolymerized natural rubber-lignin chemically bonded composite material as described in claim 2, characterized in that, The amination reagent is one of ethylenediamine, 1,6-hexanediamine, and diethylenetriamine.
4. The hyperpolymerized natural rubber-lignin chemically bonded composite material as described in claim 2, characterized in that, The raw material lignin is one of the following: alkali lignin from the papermaking industry and enzymatically hydrolyzed lignin from biorefining.
5. The hyperpolymerized natural rubber-lignin chemically bonded composite material as described in claim 1, characterized in that, The composite material also includes: 45-50 parts of carbon black, 3-6 parts of rubber processing compound activator, 1.5-3 parts of composite antioxidant, 1-2 parts of vulcanizing agent, and 1-2 parts of vulcanization accelerator.
6. The hyperpolymerized natural rubber-lignin chemically bonded composite material as described in claim 1, characterized in that, The carbon black is any one of tire-specific wear-resistant carbon black N134, N234, N220, N326, and N330; the rubber processing compound activator is prepared by uniformly blending zinc oxide and stearic acid at a mass ratio of 2:1; the composite antioxidant is a mixture of p-phenylenediamine antioxidant 6PPD and quinoline antioxidant TMQ at a mass ratio of 2:1; the vulcanizing agent is any one of powdered sulfur or insoluble sulfur OT-20; and the vulcanization accelerator is any one of sulfenamide rubber accelerators NS, DZ, and CZ.
7. The method for preparing the hyperpolymerized natural rubber / lignin chemically bonded composite material as described in any one of 1 to 6, characterized in that, include: S1: The superpolymerized natural rubber, amino-modified lignin, rubber processing compound activator, and composite antioxidant are initially mixed, and then carbon black is added and mixed continuously to obtain the compounded rubber. S2: The compound obtained in S1 is sealed and left to stand for 4-5 hours to eliminate the residual shear stress inside the rubber compound. Then, the compound is mixed with vulcanizing agent and vulcanization accelerator and kneaded to prepare the final compound. S3: The final rubber compound is molded, vulcanized, cooled and demolded to obtain a composite material.
8. The preparation method according to claim 7, characterized in that, In step S1, a closed internal mixer is used for segmented mixing. The rotor speed of the closed internal mixer is 45 r / min. The initial internal mixing is performed under pressure for 25 s. After lifting the plug and adding all the carbon black filler, the mixture is subjected to a second internal mixing under pressure for 35 s. The mixture is then continuously heated and sheared. When the rubber compound temperature reaches 150-160℃, the rubber is discharged. The total mixing time for a single batch is 3-5 min.
9. The preparation method according to claim 7, characterized in that, In step S2, a closed internal mixer is used. The rotor speed of the closed internal mixer is 30 r / min. The initial internal mixing is performed for 30 seconds. After the rubber compound is vented by lifting the plug to remove air bubbles, it is mixed again by pressing the plug. When the rubber compound is heated to 100-110℃, the rubber is discharged. The mixing time for a single batch is 2-4 minutes.
10. A heavy-duty all-steel radial tire, characterized in that: The tire tread compound is made of any one of the hyperpolymerized natural rubber / lignin chemically bonded composite materials according to claims 1 to 6.